Potential Curative Effects of Aqueous Extracts of Cissus quadrangularis (Vitaceae) and Jatropha gossypiifolia (Euphorbiaceae) on Acetaminophen-Induced Liver Injury in Mice - Romeo Joel Guemmogne Temdie, BSc, MSc, Ph.D; Edwige Ymele Chiogo Vouffo, BSc, MSc, Ph.D; Borris Rosnay Tietcheu Galani, BSc, MSc, Ph.D; Bertrand Dabole Ladane, BSc, MSc; Josee Bianzoumbe, BSc, MSc; Marc Germain Kuum Minoue, BSc, MSc, Ph.D; Fidèle Ntchapda, BSc, MSc, Ph.D; Theophile Dimo, BSc, MSc, Ph.D (Elsevier, 2023)
ABSTRACT: Background: Acetaminophen-induced liver injury remains a significant public health problem because available treatments are limited due to their adverse effects. Medicinal plants, which are an important source of bioactive molecules, could be an alternative treatment for liver disease. Objective: This study was designed to investigate the curative effect of aqueous extracts of Cissus quadrangularis (Vitaceae) and Jatropha gossypiifolia (Euphorbiaceae) on acetaminophen-induced liver injury in mice. Methods: Mice were divided into groups and treated with distilled water, silymarin (50 mg/kg), a reference hepatoprotective agent, and aqueous extracts of C quadrangularis and J gossypiifolia (50 and 100 mg/kg, PO, respectively). These substances were given as a single daily dose 4 hours after acetaminophen administration (300 mg/kg, PO) for 2 days. Mice were humanely put to death 24 hours after the last dose and serum alanine aminotransferase and aspartate aminotransferase activities, total bilirubin and protein levels, reduced glutathione, superoxide dismutase, malondialdehyde, catalase, and nitrite tissue levels were assessed. Histology of the livers of the mice was performed by hematoxylin and eosin staining. Results: Acetaminophen administration induced a significant (P < 0.05) mean (SEM) body weight loss (-14.45% [5.92%]), a significant elevation of alanine aminotransferase activity (15.08%), total protein and bilirubin levels (25.80%), and a significant (P < 0.05) increase in liver superoxide dismutase (67.71%), catalase (63.00%), glutathione (40.29%), malondialdehyde (30.67%), and nitrite levels compared with the control group. In curative treatment, C quadrangularis and J gossypiifolia (50 and 100 mg/kg) significantly (P < 0.05) reduced mean (SEM) body weight loss (16.67% [7.16%] and 1.25% [0.51%], respectively), serum alanine aminotransferase activity (17.62% and 11.14%, respectively), bilirubin level (29.62% and 49.14%, respectively) compared with acetaminophen group, and J gossypiifolia normalized serum total protein level. Both extracts significantly (P < 0.05) reduced the levels of glutathione and malondialdehyde and normalized that of nitrite, superoxide dismutase, and catalase compared with the acetaminophen group. Hepatocyte necrosis and inflammatory cell infiltration were remarkably reduced by the plant extracts. Conclusions: The results obtained are evidence in favor of the development of a formulation based on the extracts of these plants against liver diseases.